Transformation of Tn7 insertion elements across strains of Vibrio fischeri - Andrew G. Cecere; Chris Muriel-Mundo; Derek J. Fisher; Tim I. Miyashiro (PLoS ONE, 2025)
Animals typically form symbiotic relationships with bacteria that contribute to their physiology and behaviors. The ability to genetically modify these bacterial symbionts is important for investigating the molecular mechanisms that promote symbiosis establishment and maintenance. However, the molecular tools developed for laboratory-adapted strains may fail when applied to non-canonical strains. Here, we report a method to expand the use of Tn 7 site-specific transposon-insertion mutagenesis in Vibrio fischeri , which is the bioluminescent bacterial symbiont of the Hawaiian bobtail squid Euprymna scolopes . In this protocol, the laboratory-adapted strain ES114 is used as a surrogate strain for introducing genetic information into the attTn 7 insertion site. Genomic DNA extracted from the resulting strain is used as template for transformation of another strain, in which natural transformation is induced. As a proof of principle, this approach is used to complement an rpoN mutant with an IPTG-inducible rpoN construct in trans .